Irrigation channel lining using shotcrete with additives - Zhangazy N. Moldamuratov; Altaiy A. Iglikov; Mikhail N. Sennikov; Elmira B. Madaliyeva; Maira T. Turalina (Нанотехнологии в строительстве, 2022)
Introduction. Shotcrete lining is the most economical and quite fully mechanized in production among all the known varieties of concrete linings. The construction practice of hydraulic structures has accumulated numerous examples of the use of a wide variety of building materials in lining – from stone to modern films made of synthetic resins. Despite the very active efforts to find more suitable materials, concrete lining will remain the main one for a long time. Accordingly, concrete lining requires further improvements, increasing durability and reducing cost. Methods and materials. The studies were carried out by the comparison method of laboratory tests of shotcrete with nanostructured surfactants additives. In the form of nanostructured additives, SCL (sulfite-cellulose liquor), NAR (neutralized air-retaining resin), cotton soap and bitumen were used in various consistency. The tests were conducted on strength properties, shrinkage, tension deformation, adhesion strength and water permeability. Structural changes in the properties were studied by electron-microscopic analysis. Results and discussion. It is established that the optimal proportion of SCL additive to the shotcrete gauged water, under the spraying condition, is 0.5% by the cement weight. NAR additive is not observed. When cotton soap additive with gauged water are added into the shotcrete, the water content in the placed shotcrete increases as the amount of the additive added increases, the optimal cement content in the shotcrete is observed when 0.3% cotton soap additive by the cement weight is added. The “rebound” decreases when the additive proportion grows. The 0.3% SCL additive by cement weight added in 1:4 dry mixture shotcrete increases its compression strength by 16%, bending strength by 1% and tension strength by 20%. Conclusion. All nanostructured surfactant additives increase the shotcrete shrinkage. The shotcrete with SCL additive shows the smallest increase in the shrinkage, and the largest – with bitumen emulsion. The additives used in shotcrete significantly increase its tension deformability, and in a wide range reduce the values of the shotcrete instantaneous elasticity modulus, i.e. enhance its plastic properties. The surfactants and bitumen emulsion reduce the adhesion strength between shotcrete and reinforcement, however, it remains at a higher level than that of conventional concretes.